Fixing prompt corrective action - Paul H. Kupiec (American Enterprise Institute (AEI), 2016)
Prompt Corrective Action (PCA) requires regulators to sanction banks before they become insolvent and to resolve institutions within 90 days of reaching critically undercapitalized status. Forensic studies of the financial crisis conclude that the PCA process not only failed to rehabilitate troubled banks, it also produced a higher average failed-bank loss rate compared to the pre-PCA period. The most promising approach for PCA reform is to replace PCA capital ratios with a bank's nonperforming-asset coverage ratio. Research has demonstrated that this simple revision identifies failing institutions before current PCA measures which could significantly reduce Deposit Insurance Fund losses.
Keywords: A; 330; Financial regulation